Properties and Pitfalls of Various Casting MaterialsMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's MethodMaster's Method - Brendon C. Mitchell, MD; Keith Baldwin, MD (Journal of the Pediatric Orthopaedic Society of North America, 2025)
The purpose of this chapter is to thoroughly review the properties and pitfalls of various casting materials used in pediatric fracture care. Additionally, we will examine the unique characteristics of children that influence decision-making regarding the selection of materials for the under- and over-layers of a cast, as well as considerations based on anatomic location and type of cast. Generally, the underlayer of any cast provides cushioning and protects the underlying soft tissues, whereas the overlayer delivers rigid immobilization intended to maintain the alignment of the fracture. Fracture management can be achieved through splinting or casting. While splints offer rigid immobilization, they do not wrap circumferentially around the extremity, in contrast to casts, which are applied in a circumferential manner. The most common overlayer materials for achieving rigid immobilization in casting are plaster of Paris and fiberglass. Both materials can also be used to form a splint. Waterproof casting can be accomplished by using a water-tolerant underlayer (ie Gore-Tex) and a fiberglass overlayer. Proper material selection and careful application of each layer are crucial to providing immobilization in a safe manner that protects the underlying soft tissues. Key Concepts: (1) Stockinette made from a synthetic polyester material often serves as the first layer of a cast, providing an initial barrier to the skin. (2) Soft roll (ie Webril) is the primary padding material used in casting, but it can be supplemented with materials like moleskin, silicone, and foam. (3) Fiberglass and plaster of Paris offer rigid immobilization and can be used as a cast or splint, requiring careful padding to avoid soft tissue injury. (4) The art of casting requires a delicate balance of layer thickness and tautness, along with attention to cast edges, material balance, and pressure points on the skin.